PROSES DENSIFIKASI PRODUK KARBONISASI TANDAN KOSONG SAWIT MENJADI BRIKET MENGGUNAKAN CRUDE GLISEROL PRODUK SAMPING BIODIESEL SEBAGAI FILLER - Arifin, Lukman; Helwani, Zuchra; Fatra, Warman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Empty fruit bunches (EFB) has not been utilized optimally. EFB can be used as source of solid fuel in the form of briquettes. The calorific value of the EFB is 18.200,975 kJ / kg. The calorific value can be increased by carbonization process that is followed by densification process. Carbonization process aims to minimize the elements forming of the smoke, so the exhaust gas can be cleaner. Densification Process aims to increase the density and simplify the handling process. The calorific value of the combustion products can be enhanced by adding the filler. Crude glycerol is used as the filler, because it has a the calorific value of 25.175,98 kJ / kg which aims to improve the calorific value. The purpose of this research is to utilize EFB and wasting crude glycerol as a source of solid fuel, to learn how is the effect of crude glycerol, particle size, and compression pressure, to determine the influence of calorific value and compressive strength of the briquettes produced. EFB Densification uses a hydraulic press in operating conditions of particle sizes (60, 80, and 100 mesh), the composition of the filler (60:40, 70:30 and 80:20) and a pressing pressure (100.110, and 120 bar). Responses were analyzed, namely the calorific value and compressive strength by using Response Surface Methodology. The Best calorific value is obtained by 28.999,4 kJ / kg at 80 mesh particle size, composition filler 53: 47, and the pressing pressure of 110 bar. While the best compressive strength value is 9,5316 kg / cm2 at 100 mesh particle size, composition filler 60: 40, and the pressing pressure of 120 bar. Process conditions is very influence significantly on the calorific value and compressive strength is the composition of the filler and the pressing pressure.Keywords: Briquettes, Densification, Carbonization, Compressive Strength, Calorific Value, Empty Palm Bunches